A weekend with Van Gogh - Skira-Venturi, Rosabianca (New York : Distributed by St. Martin's, 1994)
In an imaginary first-person narrative, Van Gogh discusses his life and work, explaining what inspired him and how he was influenced by other artists.
Translation of: Un dimanche avec Van Gogh.
Horn Book.
Library Talk.
Wilson's Junior High School.
6.9
3-6
Keywords: Gogh, Vincent van, -- 1853-1890 -- Juvenile literature; Gogh, Vincent van, -- 1853-1890.; Gogh, Vincent van, -- 1853-1890.; Painters -- Netherlands -- Biography -- Juvenile literature; Artists; Dutch painters -- Biography